Method for modifying pore structure of agricultural waste biochar material, modified porous biochar adsorbent and application of modified porous biochar adsorbent
By mixing agricultural waste with potassium hydroxide and urea, porous biochar adsorbent is prepared, which solves the problems of low iodine capture efficiency and low material utilization in the prior art, and achieves efficient capture of gaseous, aqueous solutions and organic solvents iodine in it and show good retention and reuseability.
Patent Information
- Application Number
- CN202411417476.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art has problems such as low efficiency, high material cost and short service life in capturing and treating radioactive iodine, especially the limited iodine capture capacity of silver-based zeolites and low material utilization.
Modified porous biochar adsorbent is prepared by mixing materials such as agricultural waste walnut shells with potassium hydroxide and urea, and undergoing high-temperature reactions. It uses its rich pore structure and high specific surface area to capture gaseous, aqueous solutions and organic solvents. iodine.
The capture efficiency of gaseous iodine is significantly improved, and the capture volume can reach 3162 mg/g within 6 hours, which is 55% higher than that of unused urea samples. At the same time, modified biochar exhibits good retention and reusability under high temperature and high humidity conditions, and is suitable for the capture and treatment of radioactive iodine.
Smart Images

Figure CN119488875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iodine adsorption materials, and specifically relates to a method for modifying the pore structure of agricultural waste biochar materials and a modified porous biochar adsorbent and application thereof. Background Art
[0002] As energy demand continues to grow worldwide, nuclear energy has attracted more and more attention due to its safety, low cost, cleanliness and economy. Unfortunately, radioactive iodine is inevitably produced during the reprocessing process, which has proven to be a challenging problem for the ecosystem due to its extremely long half-life and high toxicity. In addition, radioactive iodine is easily diffused in the air and easily enriched in the human body through the food chain, which seriously endangers human health. Excessive iodine intake can cause thyroid hormone secretion disorders, easily cause thyroid hyperplasia, and may even lead to thyroid cancer. Therefore, it is urgent to explore an efficient iodine capture method. So far, liquid and solid adsorption methods have been developed to remove iodine from the environment. Liquid adsorption removes gaseous iodine through wet scrubbing technology, while solid adsorption fixes iodine through adsorbents. The advantages of the adsorption method are large adsorption capacity, simple operation, high stability and low cost, which makes the solid adsorption method the main method for treating volatile radioactive iodine.
[0003] Porous adsorbents have been added to the list of potential adsorbents to capture iodine, such as zeolites, activated carbon, macroreticular resins, activated alumina, aerogels, porous polymers, metal-organic frameworks, etc. As a common material for iodine gas capture agents, silver-loaded zeolites have been synthesized to react with iodine to form silver iodide, which has low solubility in water and high iodine capture capacity. This type of material is the most commonly used material in iodine adsorption and is also the benchmark for iodine adsorption performance. However, a small portion of iodine adsorbed by silver-based zeolites still exists in the form of iodine molecules, which are easily desorbed and migrated at high temperatures. In addition, silver is expensive, toxic, has low utilization rate, and is troublesome to regenerate after aging.
[0004] Biochar is a porous adsorption material with a high surface area and good thermal stability. Using agricultural waste as a precursor for biochar preparation is low-cost and mature technology, and more and more studies are being conducted on iodine from nuclear vapor of iodine-containing wastewater. Activation and pore formation are required during the biochar synthesis process, including water vapor activation, zinc chloride activation, and potassium hydroxide activation. Potassium hydroxide activation is considered to be a simple and effective activation method for biochar preparation. Carbon atoms are etched to produce a hierarchical porous microstructure. This method has several advantages such as lower activation temperature, shorter heat treatment time, and higher carbon yield. It is considered to be an effective method to significantly improve the porous structure of the resulting carbon material. However, potassium hydroxide has too strong an etching ability. In the process of pore formation, it not only decomposes and volatilizes the organic components in the biomass, but also easily destroys the formed biochar skeleton, resulting in poor rigidity of the material and easy powderization. Therefore, it is necessary to improve the biochar preparation method to obtain a better iodine capture effect.
[0005] In the research on the use of biochar to repair polluted water and soil, domestic scholars have proposed that adding biochar to soil can effectively increase the content of organic carbon and effective nutrients in the soil. At the same time, it can also change various physical and chemical properties of the soil, which is conducive to promoting the growth of plants and microorganisms with pollutant removal characteristics by adding biochar. However, the cycle of this repair technology is relatively long, and it is difficult to repair organic matter with high hydrophobicity and difficult biodegradation. Some scholars have tried to use alkali-activated persulfate to directly repair soil contaminated by organic matter. Although this technology successfully reduced the concentration of pesticides in the soil, due to the indiscriminate attack of free radicals on the target by the activated persulfate, the consumption of free radicals by soil particles themselves, inorganic salts in the soil, humic acid, etc., caused a large amount of persulfate waste. Corresponding to direct oxidation, leaching as another treatment technology for contaminated soil refers to the use of specific eluents to wash the contaminated soil to achieve the removal of pollutants in the soil. Therefore, it is a feasible method to remove pollutants from organic contaminated soil by leaching, and then oxidize the leaching wastewater to make it meet the discharge standards. In addition, the special functional group structure on the surface of biochar enables it to activate persulfate to degrade organic pollutants. Therefore, using biochar as an iodine capture and organic wastewater purification material can achieve the comprehensive utilization of agricultural waste and improve the efficiency of resource recycling. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a method for modifying the pore structure of agricultural waste biochar materials and a modified porous biochar adsorbent and application thereof. The porous biochar adsorbent prepared by urea-assisted KOH activation of agricultural waste walnut shells is taken as the research object, and the effect of urea on the biochar structure is explored from multiple dimensions such as skeleton rigidity, pore structure, thermal stability, nitrogen-containing functional groups, carbon matrix defects and crystal structure. Further, by changing the amount of precursors and even expanding the research objects to other biomass and other modified precursors, the intrinsic relationship between urea modification and iodine capture is revealed. The iodine capture performance of carbon nanotubes with different pore sizes and theoretical calculations are combined to fully explain the mechanism of urea in biochar iodine capture performance. It provides new ideas and references for the efficient design of high-performance materials for radioactive iodine capture.
[0007] The present invention is achieved by the following technical scheme: a method for modifying the pore structure of agricultural waste biochar materials, which comprises crushing and sieving agricultural waste, mixing the obtained biomass with potassium hydroxide and a modified precursor aqueous solution, drying and reacting the mixture at high temperature in an air-tight environment, and washing the obtained product with 0.1 mol / L hydrochloric acid and ultrapure water respectively and then drying; wherein: the modified precursor aqueous solution is a urea aqueous solution; the mass ratio of biomass to potassium hydroxide is 1:0.5-1:3, and the mass volume ratio of biomass to the modified precursor aqueous solution is 1:0.5-1:4; the temperature of the high-temperature reaction is 300-900°C; and the heating rate of the high-temperature reaction is 5°C / min.
[0008] Furthermore, the agricultural waste is any one of walnut shells, apricot shells, durian shells, sunflower discs, corn cobs or corn stalks; and the agricultural waste is crushed to 0.01-6 mm.
[0009] Furthermore, the agricultural waste is walnut shells, which are crushed to 3-6 mm. The mass ratio of the biomass to potassium hydroxide is 1:1; the mass volume ratio of the biomass to the modified precursor aqueous solution is 1:3; and the temperature of the high temperature reaction is 800°C.
[0010] The present invention also provides a modified porous biochar adsorbent obtained by utilizing the modification method.
[0011] The present invention also provides the use of the porous biochar adsorbent in capturing and removing radioactive iodine.
[0012] The radioactive iodine is gaseous iodine, elemental iodine in aqueous solution or elemental iodine in cyclohexane.
[0013] Furthermore, the radioactive iodine is gaseous iodine. The specific method is as follows: excess iodine and 0.02g of porous biochar adsorbent are placed in two small bottles respectively; then the two small bottles are placed in a large bottle; the large bottle is placed in a constant temperature box at 78°C to simulate the actual situation of nuclear fuel processing; the capture amount is determined by weight method, and the sample is weighed at regular intervals; by comparing the weight before and after capture, the capture amount of porous carbon is calculated; the calculation formula is: ; Where: q t is the adsorption capacity, mg / g; m t As porous biochar adsorbent t The mass of iodine adsorbed at each moment, g; m 0 is the initial mass of the porous biochar adsorbent, g.
[0014] The radioactive iodine is elemental iodine in aqueous solution. The specific method is as follows: 0.1 g / L porous biochar adsorbent is added to 100 mL of elemental iodine aqueous solution with a pH of 5, the reaction solution is sealed and oscillated at a speed of 160 rpm at 25° C., after a certain time interval, the supernatant is taken out and filtered through a 0.22 μm membrane to remove the porous biochar adsorbent, and the iodine element concentration in the filtrate is measured at 460 nm using a UV-visible spectrophotometer.
[0015] The radioactive iodine is elemental iodine in cyclohexane. The specific method is as follows: 0.4 g / L porous biochar adsorbent is added to 100 mL of cyclohexane solution of 100 mg / L elemental iodine, the reaction solution is sealed and oscillated at 160 rpm at 25°C, after a certain time interval, the supernatant is taken out and filtered through a 0.22 μm membrane to remove the biochar, and the iodine concentration in the filtrate is measured at 523 nm using a UV-visible spectrophotometer.
[0016] The present invention crushes and sieves agricultural waste, mixes the obtained biomass with a certain amount of potassium hydroxide and a modified precursor aqueous solution, and then reacts at high temperature in an air-tight condition after drying. The obtained product is washed and dried. The present invention utilizes agricultural waste as a resource, and the obtained biochar material has a good removal effect on iodine in gaseous, aqueous and organic solvents, showing that the biochar material has extremely high iodine capture activity and a wide range of applications. The value-added utilization of agricultural waste is improved; the preparation method is simple, easy to industrialize, and has industrial application prospects.
[0017] The addition of urea during KOH activation can effectively promote the iodine capture performance of walnut shell biochar, and the capture of gaseous iodine reaches 3162 mg / g within 6 hours, which is 55% higher than the capture of 2027 mg / g of the sample without urea. After optimizing the KOH dosage, urea-assisted biochar prepared with other biomass such as walnut shell, apricot shell, durian shell, sunflower disk, corn stalk and corn cob as precursors achieved similar effects, and the capture of gaseous iodine reached 5068 mg / g, 5368 mg / g, 6177 mg / g, 5505 mg / g, 5518 mg / g and 6212 mg / g, respectively, proving that the addition of urea significantly promotes the iodine capture performance of biochar. Mechanism studies show that the use of urea does not increase the nitrogen-containing functional groups of biochar, but enhances the skeleton rigidity of biochar, increases the specific surface area and pore volume of biochar, and especially enriches the hierarchical pore structure. The results of iodine capture experiments, characterization comparison of biochar with and without urea modification, and density functional theory calculations indicate that the microporous structure is the main reason for the high iodine capture performance of urea-assisted biochar, rather than the chemical affinity brought by heteroatom doping. The kinetic and isotherm model fitting results show that the adsorption process is mainly physical adsorption, and monolayer adsorption is the main one. Thermodynamic analysis shows that adsorption is an exothermic and spontaneous process. The present invention provides theoretical support for the removal and recovery technology of gaseous and liquid radioactive iodine. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0019] Figure 1 Schematic diagram of the synthesis process and iodine capture of porous carbon; Figure 2 The SEM and EDS images of porous carbon; in the figure: (a) is the SEM image; (b) is the EDS element content image; Figure 3 BET, XPS and XRD spectra of porous carbon; in the figure: (a) N2 adsorption-desorption isotherms of WS-Urea and WS-KOH; (b) pore size distribution of WS-Urea and WS-KOH; (c) XPS total spectrum of WS-Urea; (d) C 1s high-resolution XPS spectrum of WS-Urea; (e) O 1s high-resolution XPS spectrum of WS-Urea; (f) XRD spectrum of WS-Urea and WS-KOH; Figure 4The capture performance of porous carbon on gaseous iodine; in the figure: (a) is the effect of different porous carbons; (b) is the effect of different urea ratios; (c) is the effect of different temperatures; (d) is the effect of different precursors; (e) is the effect of carbon nanotubes with different pore sizes; (f) is the effect of water vapor; Figure 5 The retention performance of WS-Urea@I at room temperature and ambient pressure for 7 days; Figure 6 Characterization analysis diagram of iodine capture by porous carbon; in the figure: (a) is the thermogravimetric curve before and after WS-Urea captures iodine; (b) is the XRD spectrum before and after WS-Urea captures iodine; (c) is the XPS total spectrum before and after WS-Urea captures iodine; (d) is the I 3d high-resolution XPS spectrum before and after WS-Urea captures iodine; (e) is the Raman spectrum before and after WS-Urea captures iodine; (f) is the O 1s high-resolution XPS spectrum before and after WS-Urea captures iodine; Figure 7 Schematic diagram of the mechanism of iodine capture on WS-Urea; Figure 8 The desorption and cycle performance of porous carbon for gaseous iodine; in the figure: (a) is the desorption of gaseous iodine at 120°C for WS-Urea, WS-KOH and WS-C; (b) is the cycle performance of gaseous iodine capture at 78°C for WS-Urea, WS-KOH and WS-C; Fig. 9 The capture performance and model fitting of iodine by porous carbon in cyclohexane; in the figure: (a) is the capture of iodine by different porous carbons in cyclohexane; (b) is the pseudo-first-order and pseudo-second-order kinetic models of WS-Urea; (c) is the Langmuir and Freundlich isotherm models of WS-Urea; (d) is the thermodynamic model of WS-Urea; Fig.10 This is a graphite model structure diagram. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0022] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0023] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0024] 1. Experimental materials and reagents: Walnut shell (WS) was from Luliang, Shanxi Province, KOH was purchased from Tianjin Komiou Chemical Reagent Co., Ltd., cyclohexane was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., urea (Urea) and elemental iodine (I2) were purchased from Sinopharm Chemical Reagent Co., Ltd., hydrochloric acid (HCl) was purchased from Shanghai Wokai Biotechnology Co., Ltd., and carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. The experimental water was ultrapure water. Nuclear-grade activated carbon was provided by the China Institute of Radiation Protection.
[0025] Experimental instruments: electronic analytical balance (ME204E, Shanghai Mettler Toledo Instruments), electric blast drying oven (DHG-9145A, Shanghai Yiheng Technology Co., Ltd.), tubular furnace (OTF-1200X, Hefei Kejing Material Technology Co., Ltd.), circulating water multi-purpose vacuum pump (SHB-ⅢG, Zhengzhou Great Wall Science and Technology Industry and Trade Co., Ltd.), ultraviolet visible spectrophotometer (UV-8000S, Shanghai Yuanxi Instrument Co., Ltd.), full temperature oscillating incubator (HZQ-D180, Suzhou Peiying Experimental Equipment Co., Ltd.), pH meter (FE28-TRIS, Mettler Toledo Instrument Co., Ltd.), etc.
[0026] 2. Experimental Methods 1. Biochar preparation: Walnut shells were washed with ultrapure water before use, dried and crushed, and sieved to obtain fragments of 3-6 mm. After that, 1.0 g of walnut shell biomass was dispersed in 20 ml of deionized water with 1.5 g of KOH and 2.0 g of urea, and the mixture was stirred slowly and evenly mixed. After natural drying at room temperature, it was dried at 80 ° C in a blast drying oven for 12 h, and then continued to be dried at 120 ° C for 2 h. The walnut shells were then placed in a tube furnace and reacted at 800 ° C for 2 hours under argon protection, with a heating rate of 3 ° C / min. After cooling to room temperature, it was washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH no longer changed. Finally, the washed sample was dried in a blast drying oven to obtain a modified porous biochar adsorbent, which was subsequently recorded as WS-Urea.
[0027] The other preparation methods are the same, and the porous carbon prepared in the absence of urea is recorded as (WS-KOH), and the porous carbon prepared in the absence of urea and KOH is recorded as (WS-C).
[0028] Urea was replaced by dicyandiamide, melamine, boric acid, thiourea and pyridine boronic acid, and the other preparation methods were the same, so as to investigate the effects of several other organic precursors commonly used for doping, such as dicyandiamide, melamine, boric acid, thiourea and pyridine boronic acid, as auxiliary activation precursors.
[0029] The other preparation methods were the same, and the walnut shells were replaced with other biomass such as apricot shells, durian shells, sunflower discs, corn stalks and corn cobs to prepare biochar and investigate the universality of this modification method.
[0030] 2. Characterization and analysis: The biochar was characterized by field emission scanning electron microscopy (SEM, ZEISS Sigma 300, Germany), fully automatic specific surface and porosity analyzer (Micromeritics ASAP 2460, USA), X-ray photoelectron spectrometer (XPS, ThermoScientific K-Alpha, USA), X-ray diffractometer (Panalytical Aeris, Netherlands), Raman spectrometer (Horiba LabRAM HR Evolution, Japan), Fourier transform infrared spectrometer (PerkinElmer SpectrumTwo, USA), and thermogravimetry (Netzsch STA 449 F3, Germany). All binding energies were calibrated with the C1s peak at 284 eV after XPS test as reference.
[0031] 3. Iodine capture performance test: Gaseous iodine capture experiment: Figure 1 As shown, excess iodine and porous biochar adsorbent (0.02 g) were placed in two small weighing bottles (25 mm × 25 mm), respectively. The two small bottles were then placed in a large weighing bottle (70 mm × 35 mm). The large weighing bottle was placed in a constant temperature box at 78 ° C to simulate the actual situation of nuclear fuel processing. The capture amount was determined by the weight method, and the samples were weighed at regular intervals. By comparing the weight before and after capture, the capture amount of the porous biochar adsorbent was calculated. Each group of experiments was carried out three times, and the experimental results were averaged. The calculation formula is shown in (1): ; Where: q t is the adsorption capacity, mg / g; m t As porous biochar adsorbent t The mass of iodine adsorbed at each moment, g; m 0 is the initial mass of the porous biochar adsorbent, g.
[0032] Elemental iodine aqueous solution capture experiment: It was carried out in a 150 mL iodine volumetric flask. 100 mL of elemental iodine aqueous solution with pH = 5 was added, and then 0.1 g / L of porous biochar adsorbent was added. The reaction solution was sealed and placed in a constant temperature oscillator, and the reaction was oscillated at 160 rpm at 25°C. After a certain time interval, the supernatant was taken out and filtered through a 0.22 μm membrane to remove the porous biochar adsorbent, and the iodine concentration in the filtrate was measured at 460 nm using a UV-visible spectrophotometer.
[0033] Elemental iodine capture experiment in cyclohexane solvent: It was carried out in a 150 mL iodine volumetric flask. 100 mL of cyclohexane solution of elemental iodine was added, and then 0.4 g / L of porous biochar adsorbent was added. The reaction solution was sealed and placed in a constant temperature oscillator, and the reaction was oscillated at 160 rpm at 25°C. After a certain time interval, the supernatant was taken out and filtered through a 0.22 μm membrane to remove the porous biochar adsorbent, and the iodine concentration in the filtrate was measured at 523 nm using a UV-visible spectrophotometer.
[0034] 4. Adsorption kinetics experiment: 0.4 g / L of porous biochar adsorbent was added to 100 mg / L iodine-containing cyclohexane solution. Its absorbance was measured at regular intervals and fitted using pseudo-first-order kinetics and pseudo-second-order kinetics models. The calculation formulas are shown in (2) and (3): ; Where: q t for t Adsorption capacity at the time, mg / g; t is time, min; q e is the equilibrium adsorption capacity, mg / g; k 1 Pseudo-first-order kinetic adsorption rate constant, min -1 ; k 2 is the pseudo-second-order adsorption rate constant, g / (mg·min).
[0035] Adsorption isotherm experiment: 0.4 g / L porous biochar adsorbent was added to cyclohexane solutions containing different iodine concentrations, and the absorbance was measured after adsorption equilibrium. The Langmuir and Freundlich models were used to fit the data, and the calculation formulas are shown in (4) and (5): ; Where: q e is the equilibrium adsorption amount, mg / g; C e Concentration of the solution after adsorption equilibrium, mg / L; q max is the maximum theoretical adsorption capacity, mg / g; KL is the Langmuir model constant, L / mg; K F is the Freundlich model constant, L 1 / n mg 1-(1 / n) / g; n is a linear constant.
[0036] Adsorption thermodynamics experiment: 0.4 g / L of porous biochar adsorbent was added to 100 mg / L of iodine-containing cyclohexane solution and reacted in a full-temperature shaking incubator at 25°C, 35°C, and 45°C. After equilibrium, the absorbance was measured. The data were fitted using thermodynamic equations, as shown in (6) and (7): ; Where: ∆G 0 is the Gibbs free energy, kJ / mol; ∆H 0 is the standard enthalpy change, kJ / mol; ∆S 0 is the standard entropy change, J / (mol·K); R Universal gas constant, 8.314 J / (mol·K); T is the absolute temperature, K; K d is the thermodynamic equilibrium constant (dimensionless). radioactive isotopes 129 I and 131 I is harmful to humans and its chemical and electronic properties are similar to those of non-radioactive iodine isotopes. 127 I is similar. Therefore, for safety reasons, most studies currently use non-radioactive iodine isotopes. 127 I was used as an alternative. This experiment was performed in triplicate and the average value was taken. The error bars represent the standard deviation of the three experiments.
[0037] 5. Density functional theory (DFT) calculations: DFT calculations were performed in the DMol3 module in Materials Studio software, using the full electron spin polarization method. The calculations used the generalized gradient approximation (GGA) and the Perdew-Burke-Ernzerhof (PBE) electron exchange correlation function. In addition, the van der Waals correction method of DFT-D was used to describe long-range electrostatic interactions, and the convergence criterion was chosen to be 10 -5 Ha, the maximum force is 0.002 Ha / Å, and the maximum displacement is 0.005 Å. The k-points are set to 2×2×1 using the Monkhorst-Pack method. The adsorption energy E ad Defined as: E ad = E host / adsorbate -E host -Eadsorbate , where E host / adsorbate 、E host and E adsorbate They represent the energy of the adsorbed structure, the adsorbent body and the adsorbate itself respectively.
[0038] 3. Experimental Results 1. Structural characterization of urea-assisted walnut shell biochar: Surface structure Figure 2 As shown, (a) is a scanning electron microscope image, which shows that it has a large number of pore structures, and after being pyrolyzed at 800°C, it can still maintain its complete shape, and a large number of grooves appear on the surface, which significantly increases its specific surface area, which is an indispensable advantageous structure as a porous adsorbent. According to previous studies, these porous structures are due to the generation of K2CO3 gas by KOH and the carbon matrix at temperatures above 500°C, and the reaction can be expressed as 6KOH+C↔3H2+2K2CO3. In this process, the carbon material is etched to obtain a higher specific surface area. Urea reacts with K2CO3 at 600~800°C to generate a heterocyclic group of pyridine-N. Under high temperature, the heterocyclic group of pyridine-N is pyrolyzed to generate NH3, and this process further promotes the formation of the pore structure. Figure 2 (b) is the element distribution diagram of the EDS test results, showing that the carbon (C) content is 95.81%, the oxygen (O) content is 4.19%, and the nitrogen (N) content is 0%. This shows that the nitrogen-containing groups have successfully transformed into NH3, producing a large number of porous structures. This also reveals the main reason why the nitrogen element was not detected in the EDS analysis.
[0039] 2. Pore structure analysis: Figure 3 As shown in Figure 2, pore structure is an important indicator for measuring the performance of porous carbon. Figure 3 (a) It can be seen that the porous carbon in the relative pressure region ( p / p 0 <0.05) for N2 adsorption increased rapidly and then tended to be flat. Among them, the increasing trend of WS-Urea for N2 adsorption was significantly higher than that of WS-KOH. And they belong to the classic type I and type IV adsorption isotherms, indicating that both are mainly microporous structures, and WS-Urea has more microporous structures than WS-KOH. From the test results, it can be seen that with the assistance of urea, the specific surface area (S BET ) and micropore volume (V micro ) were significantly improved, S BET From 1539.16cm 2 / g increased to 3395.97cm 2 / g,V micro From 0.57cm 3 / g increased to 1.39cm 3 / g. This is consistent with the EDS results, indicating that the increased N-containing groups lead to a richer pore structure in the porous carbon through the auxiliary effect of urea, giving the porous carbon a higher specific surface area and micropore volume. The micropore distribution of porous carbon was analyzed by the Saito-Foley method (see Figure 3 (b)), it was found that the pore sizes of both are mainly distributed at 0.69nm and 0.74nm, indicating that WS-Urea has more and smaller micropore structures.
[0040] Chemical surface composition: Analysis of the properties and characteristics of porous carbon through XPS test results. Figure 3 (c) shows that WS-Urea is mainly composed of carbon, oxygen and trace nitrogen, with contents of 91.45%, 7.87% and 0.68% respectively, which is similar to the EDS test results. Figure 3 (d) It can be seen that CC / C=C (284.80 eV) has the highest content, while COC (286.44 eV) and OC=O (287.92 eV) have lower contents.
[32] , O1s high-resolution spectrum Figure 3 In (e), 531.7 eV, 532.93 eV, and 534.39 eV are respectively assigned to OC=O, CO / OH, and C=O
[33] These results indicate that the carbon skeleton is more prominent under high-temperature and oxygen-deficient preparation conditions, and further verify that high temperature leads to a decrease in nitrogen content, which in turn promotes the formation of a porous structure.
[0041] Phase analysis: XRD spectrum of porous carbon is as follows Figure 3 As shown in (f), both WS-Urea and WS-KOH show two broad peaks near 23° and 46°, corresponding to the (002) and (100) diffraction patterns of amorphous carbon materials. This indicates that both have a tendency to graphitize during the carbonization process. Since the diffraction peaks are wide and the degree of graphitization is relatively low, it can be inferred that both are staggered amorphous carbon materials. WS-Urea has a lower diffraction peak intensity at low diffraction angles. This result indicates that the auxiliary effect of urea has significantly changed the structure of the carbon skeleton, making it more disordered than WS-KOH. The higher intensity of WS-Urea relative to WS-KOH at low diffraction angles is attributed to the presence of more micropores, which is consistent with the BET results.
[0042] Therefore, the promotion of urea on the iodine capture performance of biochar is mainly due to the improvement of pore structure rather than the chemical affinity caused by nitrogen-containing functional groups.
[0043] 3. Considering that urea does not increase the amount of heteroatom doping on biochar, but adjusts the pore structure of biochar to play an auxiliary activation role, the effects of several other organic precursors commonly used for doping, such as dicyandiamide, melamine, boric acid, thiourea and pyridine boric acid, as auxiliary activation precursors were investigated. Dicyandiamide and melamine have -NH2 functional groups similar to the structure of urea, and the number of N atoms contained in a single molecule of dicyandiamide and melamine is 2 times and 3 times the number of N atoms in the urea molecule, respectively. However, the iodine capture effect of biochar prepared with dicyandiamide and melamine as precursors is lower than that of urea, indicating that the auxiliary pore-forming effect of dicyandiamide and melamine is lower than that of urea. Further replacing urea with boric acid did not improve the gaseous iodine capture effect of the obtained biochar. The joint modification of N and B provided by pyridine boric acid and the joint modification of N and S provided by thiourea did not further improve the activity. As shown in Table 4, the pore structure analysis of biochar prepared by modified precursors shows that the biochar modified by urea has the highest specific surface area and pore volume, which may be an important reason why urea-modified biochar has high iodine capture performance.
[0044] 4. Gaseous iodine capture performance: using Figure 1 The equipment was used for the experiment. Figure 4 (a) It can be seen that in the early stage of capture, the capture amount of WS-Urea and WS-KOH increased rapidly and basically reached equilibrium at 3h. The capture rate of WS-C is relatively slow, which may be due to the fact that WS-Urea and WS-KOH have richer pore structures compared with WS-C, and these pores are conducive to the diffusion of iodine molecules. In addition, the 6h capture amount of iodine by WS-Urea, WS-KOH and WS-C is 3161mg / g, 2143mg / g and 503mg / g, respectively. The iodine capture ability of WS-Urea is higher than that of most of the materials reported so far (see Table 1). It also shows that the porous carbon prepared by urea-assisted KOH improves the iodine capture performance.
[0045] Table 1: Iodine capture capacity of different materials Comparison of iodine capture by porous carbon prepared with different urea ratios (see Figure 4 (b) As can be seen from the figure, as the urea ratio increases, the capture amount gradually increases. When the walnut shell: potassium hydroxide: urea ratio is 1:1.5:3, the capture amount reaches the maximum value (5068 mg / g), but when the amount of urea continues to increase, the capture amount decreases. The pore size analysis of these two porous carbons (see Table 2) shows that 1:1.5:3 has a larger S BET 、V microand a smaller average pore size. This indicates that excess urea can cause porous carbon to produce more mesopores and macropores, while the improvement in iodine capture performance may be caused by micropores. Since walnut shells are widely available and can achieve the effect of treating waste with waste, and considering the economic benefits, the present invention mainly studies the case of a ratio of 1:1.5:2.
[0046] Table 2: Pore structure parameters of porous carbon with different urea ratios like Figure 4 (c) The iodine capture performance of porous carbon at different activation temperatures was studied using a ratio of walnut shell: potassium hydroxide: urea of 1:1.5:3. The results show that the capture amount gradually increases with increasing temperature and reaches a maximum value (6248 mg / g) at 900°C. Pore size analysis of different activation temperatures (see Table 3) shows that the average pore size gradually decreases with increasing temperature, indicating that high-temperature activation helps porous carbon form more microporous structures, and smaller pore sizes are conducive to iodine capture. Although S at 300°C BET and V micro Below 600°C, however, the iodine capture capacity is high, and studies have shown that high temperatures may have an adverse effect on the functional groups of porous carbon.
[50] Therefore, it can be inferred that the functional group may play a dominant role in iodine capture at 300°C. The specific surface area increases significantly at an activation temperature higher than 500°C compared to 300°C and 400°C, which verifies the above statement that when the temperature is higher than 500°C, KOH etching of the carbon matrix promotes the formation of a pore structure. Too high an activation temperature is not conducive to economic benefits and practical applications, so the present invention mainly studies an activation temperature of 800°C.
[0047] Table 3 Pore structure parameters of porous carbon at different activation temperatures The porous carbon prepared using different precursors also has a significant effect on the iodine capture performance (see Figure 4 (d) At an activation temperature of 800°C, when the ratio of walnut shell: potassium hydroxide: urea was 1:1.5:3, it was found that the porous carbon with urea as the precursor had the largest iodine capture capacity (5068 mg / g). High temperature treatment usually leads to a reduction in functional groups in porous carbon, so the pore structure is particularly important for the capture capacity. As can be seen from Table 4, the capture capacity increases with S BET With V microThis further verifies the importance of specific surface area and micropores in iodine capture. In addition, the porous carbon prepared with urea as a precursor has a larger specific surface area, which is related to the NH3 formed by the pyridine-N heterocyclic group generated during the pyrolysis of urea, which helps to promote the formation of pore structure. This is consistent with the above.
[0048] Table 4: Pore structure parameters of porous carbon from different precursors Since the pores on biochar are hierarchical and mainly micropores, in order to confirm the contribution of micropores to iodine adsorption, we used carbon nanotubes with various pore sizes (see Table 1) as research objects to investigate the effect of pore size on gaseous iodine adsorption. Figure 4 As shown in (e), when the pore size of carbon nanotubes is in the micropore range of 1-2 nm, the adsorption capacity of gaseous iodine can reach 1958 mg / g; when using carbon nanotubes with a larger pore size of 2-4 nm in the mesopore range, the iodine capture capacity drops rapidly to only 655 mg / ; the pore size of the carbon nanotubes used is further increased to even >50 nm, and the iodine adsorption capacity of carbon nanotubes continues to drop to. With the increase of pore size, the iodine capture performance of carbon nanotubes gradually weakens. Among them, the saturated capture capacity of single-walled carbon nanotubes (1~2nm) for iodine is 1958 mg / g, which is significantly better than carbon nanotubes with other pore sizes. This further indicates that micropores have more advantages in the capture of iodine, while mesopores and macropores play an auxiliary role. Through BET testing, WS-Urea has more and smaller micropores than WS-KOH, and its specific surface area is also larger, so WS-Urea performs better in iodine capture.
[0049] Radioactive iodine vapor is usually discharged from high-temperature and high-humidity pipes. To simulate this state, we added sufficient water to a closed weighing bottle to explore whether the water vapor formed under high temperature conditions would affect the performance of porous carbon in the iodine capture process. Figure 4 As shown in (f), water vapor has a negative impact on the iodine capture performance of both porous carbons. Compared with the case without humidity, the iodine capture of WS-Urea and WS-KOH decreased by 17.49% and 35.79%, respectively. The results show that water vapor has little effect on the iodine capture ability of WS-Urea, so the porous carbon prepared with the assistance of urea has greater practical application value.
[0050] like Figure 5We conducted retention performance tests to explore whether the capture phenomenon occurred in the internal pores or surface condensation. The iodine-loaded WS-Urea (WS-Urea@I) was exposed to air at room temperature and ambient pressure. The results showed that the retention rate of WS-Urea@I was 85.41% after 7 days, showing a good retention effect. This shows that the iodine capture is not due to surface condensation, but is caused by the interaction between WS-Urea and iodine molecules.
[0051] For radioactive iodine capture, the material is required to have as low a desorption rate as possible after capturing iodine to avoid secondary contamination during transfer and storage. The iodine-captured WS-Urea (WS-Urea@I) was placed in a fume hood at room temperature to measure its mass change. When the standing time was 24 hours, the iodine desorption rate was only 2.91%. Further extending the standing time from 1 day to 7 days, the cumulative desorption rate of iodine gradually increased, reaching 8.72% on the 7th day, indicating that WS-Urea (WS-Urea@I) has a good anti-desorption effect on the captured iodine at room temperature. Of course, this result does not mean that WS-Urea (WS-Urea@I) cannot be used for ordinary iodine-containing waste treatment. If WS-Urea (WS-Urea@I) is placed at a higher temperature (>78°C) or in an organic solvent such as methanol or cyclohexane, the captured iodine can also be quickly desorbed, thereby realizing the recovery of iodine and the reuse of WS-Urea (WS-Urea@I).
[0052] 4. Capture mechanism of gaseous iodine by porous carbon: In order to analyze the capture mechanism of porous carbon, we characterized and analyzed WS-Urea before and after adsorption by thermogravimetry, XRD, Raman spectroscopy and XPS. Figure 6 (a) is a thermogravimetric analysis conducted under argon conditions, which shows that about 15% of the weight is lost at 800°C. This is due to the high-temperature calcination treatment in a tubular furnace, which makes WS-Urea show excellent thermal stability, which is crucial for the capture of iodine in high-temperature environments such as nuclear power plant exhaust and flue gas. In addition, WS-Urea@I loses 69.11% of its mass between 50 and 200°C. According to reports, this is caused by the sublimation of iodine physically adsorbed in porous carbon. Therefore, it can be inferred that the adsorption of iodine is mainly physical adsorption. Figure 6 (b) shows the XRD patterns of WS-Urea before and after it captures iodine. The peak intensity decreases due to the adsorption of iodine on the surface, which indicates that iodine has been successfully captured by the porous carbon. In order to further study the interaction mechanism of porous carbon with iodine, XPS tests were performed on WS-Urea@I. Figure 6 (c) It can be clearly seen that the porous carbon after adsorption shows the characteristic peak of iodine, which further confirms that iodine has been captured by the porous carbon. Figure 6 (d) is a high-resolution image of iodine after porous carbon captures iodine. It can be seen that I2 and I3 - Two characteristic peaks are shown at 620.73eV, 632.13eV and 618.83eV, 630.48eV respectively. This shows that iodine exists mainly in the form of iodine molecules in porous carbon materials, followed by the form of polyiodide anions, which is consistent with the TGA analysis results, and further proves that the capture of iodine is mainly physical adsorption. Raman spectroscopy also further proves this point. Figure 6 (e) It can be seen that at about 170cm -1 The peaks near are attributed to the iodine molecules inside the pores. -1 The peak value indicates that there is I3 - The existence of 170cm -1 The peak area is much higher than 100 cm -1 , indicating that the interaction between iodine molecules leads to the formation of a closed iodine solid structure in the middle of the pores. Therefore, the high specific surface area of porous carbon, especially micropores, plays an important role in improving the capture of gaseous iodine. Figure 6 (f) shows the high-resolution spectrum of O1s before and after the adsorption of iodine. Due to the effect of iodine, the three peaks shifted to varying degrees. This may be the effect of carbonyl, hydroxyl, etc. in the adsorption of iodine. Among them, the peak of -OH shifted from 523.93eV to 532.72eV, indicating that the interaction between -OH occupying most of the oxygen-containing functional groups and iodine led to an increase in electron density, which played a decisive role in the adsorption of iodine. According to the Lewis acid-base theory, the iodine molecule acts as a Lewis acid, and the -OH with a lone pair of electrons acts as a Lewis base. Therefore, there is a strong interaction between the iodine molecule and -OH. The reaction process can be expressed as: porous carbon -OH+1.5I2→porous carbon -OH…I3 - ...I2→porous carbon-OH...I3 - .
[0053] In summary, the capture mechanism of gaseous iodine by porous carbon is as follows: Figure 7 As shown, it can be shown that porous carbon with porous structure, especially micropores, plays a major role in the adsorption of iodine. In addition, adsorption sites mainly composed of hydroxyl groups can also produce a small amount of chemical adsorption of iodine.
[0054] 5. Recyclability of porous carbon for gaseous iodine capture: Currently, heating method or organic solvent (ethanol, hexane) is often used to explore the recyclability of iodine-loaded capture agents. This study used the heating method to investigate the iodine recycling performance. Figure 8(a) It can be seen that WS-Urea basically reached desorption equilibrium at 300 min, with a desorption rate of up to 98.98%. Its outstanding iodine desorption rate laid the foundation for the next capture. WS-Urea has a higher desorption rate than WS-KOH and WS-C, which may be related to the newly formed micropores and mesopores in the urea-assisted process. Figure 8 (b) After 5 cycles, the adsorption rates of iodine by WS-Urea and WS-KOH decreased by 8.13% and 8.63% respectively, and the capture of iodine remained at a high level, but WS-C decreased by 48.75%. The results show that the porous carbon has higher reusability under the action of potassium hydroxide and urea, and therefore has a broader application prospect.
[0055] 6. Porous carbon adsorption performance on cyclohexane iodine solution: Radioactive iodine exists not only in the atmosphere but also in water. Cyclohexane can stabilize iodate in the solution, so cyclohexane solution containing iodine is used for liquid research to ensure the accuracy of the experiment. Fig. 9 (a) When the iodine concentration is 100 mg / L, the three porous carbons basically reach saturation within 10 minutes. WS-Urea performs best, with a removal rate of 86.62% at 90 minutes, while the removal rates of WS-KOH and WS-C are 80.93% and 39.96%, respectively. The experimental results show that in the iodine solution of cyclohexane, the porous carbon prepared with the assistance of urea has more advantages.
[0056] Adsorption kinetics of porous carbon in cyclohexane iodine solution: Fig. 9 As shown in (b), the adsorption capacity of porous carbon increases rapidly in the first 5 minutes, and then the growth trend becomes gentle, and it basically reaches equilibrium at 10 minutes. The equilibrium adsorption capacity is 216.56 mg / g. The adsorption time of this porous carbon is fast, which highlights its superior performance in practical applications. Studies have shown that the adsorption rate of molecules depends on their mobility in the solution, the pore structure of the adsorbent, and the fluid dynamics contact between the solution and the particle phase. The huge specific surface area and pore volume of porous carbon allow the iodine solution to enter quickly, thereby quickly adsorbing iodine molecules. According to the kinetic fitting results and related parameters, see Fig. 9 (b) and Table 5, the porous carbon is in good agreement with the pseudo-first-order kinetic model ( R 2 =0.9996), the actual equilibrium adsorption capacity (216.56 mg / g) is consistent with the fitted theoretical maximum adsorption capacity (214.73 mg / g), indicating that it is mainly physical adsorption, which is the same as our expectation.
[0057] Table 5: Nonlinear fitting parameters of pseudo-first-order and pseudo-second-order kinetic models 7. Adsorption isotherm of porous carbon in cyclohexane iodine solution: The present invention adopts Langmuir and Freundlich isotherm models for fitting. They are the most common models in adsorption isotherm research and can usually describe the situation at various concentrations. The Langmuir isotherm model indicates that the surface of the adsorbent is uniform, and each adsorbate does not interfere with each other, which is a uniform monolayer equilibrium adsorption. The Freundlich model refers to the adsorption process on a non-uniform surface and is not limited to the monolayer adsorption capacity. The results of fitting the test data by Langmuir and Freundlich equations are shown in 9(c) and Table 6. It can be seen that as the concentration of iodine increases, the amount of iodine adsorbed by porous carbon gradually increases. And the porous carbon fits the Langmuir model better (R 2 =0.9968), according to the Langmuir model hypothesis, it shows that the adsorption process is mainly monolayer adsorption. The basic characteristics of the Langmuir adsorption model can be expressed by the equilibrium constant R L The calculation formula is shown in (8): ; In the formula, K L is the Langmuir model constant, L / mg; C 0 is the iodine concentration in the initial solution, mg / L. R L Indicates adsorption type, 0< R L <1 indicates good adsorption performance. R L = 0 means irreversible adsorption, R L =1 means reversible adsorption and the adsorption isotherm is linear. R L >1 indicates poor adsorption performance. From Table 6, we know that K L =5.02×10 -3 ,0< C 0<500, calculated from formula (8) The values are all greater than 0 and less than 1. This shows that the porous carbon has good adsorption properties.
[0058] Table 6: Nonlinear fitting parameters of isotherm model 8. Adsorption thermodynamics of porous carbon in cyclohexane iodine solution: Fig. 9 (d) and Table 7 show that the van't Hoff equation is fitted to obtain R 2 =0.9999, the fitting effect is good. ∆G 0The negative value of indicates that the adsorption of iodine by WS-Urea is a spontaneous process. ∆G 0 The absolute value of is less than 40 kJ / mol, indicating that the adsorption process is mainly a physical process.
[61] , which is consistent with the kinetic model hypothesis. ∆H 0 A negative value indicates that the adsorption process is promoted at lower temperatures and is exothermic. ∆S 0 A positive value indicates that the randomness of the solid-liquid interface increases during the adsorption process.
[0059] Table 7: Thermodynamic parameters fitting parameters 9. Study on the dominant role of micropores in hierarchical pores in biochar iodine capture: Since the pores on biochar are hierarchical pores and are mainly micropores, in order to confirm the contribution of micropores to iodine adsorption, we used carbon nanotubes with various pore sizes as research objects to examine the effect of pore size on gaseous iodine adsorption. Figure 4 (e) It can be seen that when the pore size of carbon nanotubes is in the microporous range of 1-2 nm, the adsorption of gaseous iodine can reach 1958 mg / g; when using carbon nanotubes with a larger pore size of 2-4 nm in the mesoporous range, the iodine capture amount drops rapidly to only 655 mg / ; the pore size of the carbon nanotubes used is further increased to >50 nm, and the iodine adsorption of carbon nanotubes continues to drop to. The above results show that the smaller the pore size, the more conducive it is to the adsorption of iodine, thus proving that the micropores in the hierarchical pores play a leading role in the iodine capture of biochar.
[0060] Table 8: DFT calculation results of iodine molecule adsorption energy for different interlayer structures In order to verify this result, the adsorption of iodine on the graphite surface with different interlayer spacing was theoretically calculated using graphite as a model. According to the DFT calculation results, when the interlayer spacing (d) is 0.33 nm, the graphite layer is severely distorted and deformed, and it is difficult for iodine to enter the graphite interlayer ( Fig.10 ), which means that pores smaller than iodine molecules will hinder the effective adsorption of iodine; when the interlayer spacing matches the kinetic diameter of the iodine molecule, the binding energy is most negative ( Fig.10, Table 8), indicating that this size of pores is conducive to the adsorption of iodine. The binding energy continues to increase as the interlayer spacing continues to increase to 2.5 nm, indicating that too large an interlayer spacing (corresponding to the pore size of biochar) is not conducive to the adsorption of iodine, supporting the conclusion of the experimental results that micropores dominate the adsorption of iodine. Nevertheless, considering that when multiple iodine molecules enter at the same time, once these pores are blocked by iodine during the iodine adsorption process, more iodine molecules cannot fill the entire pore, and the accessibility of the pores will be limited. In addition, since the DFT model calculation does not take into account the influence of the solvent, considering that in aqueous solution or organic solvents, the actual size of the iodine molecule becomes larger due to the interaction between the solvent molecules and iodine, the pore size of the biochar should be 2 to 4 times the kinetic size of the iodine molecule.
[0061] In summary, the porous carbon prepared by urea-assisted potassium hydroxide in the present invention has an ultra-high specific surface area and micropore volume, and its iodine capture performance is significantly improved compared to the porous carbon prepared by KOH modification. In the capture of gaseous iodine, the porous carbon 6h capture amount is 3161mg / g, and the maximum capture amount can reach 6248mg / g through the improvement of preparation technology. For iodine in cyclohexane solution, the 90min adsorption amount is 216.56mg / g, and the adsorption process conforms to the pseudo-first-order kinetic model and the Langmuir isotherm model, indicating that the adsorption process is physical adsorption, and monolayer adsorption is the main, and thermodynamics also shows that the adsorption process is spontaneous.
[0062] The iodine loaded on the porous carbon mainly exists in the form of iodine molecules, with a small amount of polyanions. The capture of gaseous iodine is mainly through physical adsorption, in which micropores play a leading role in the capture process, and a small amount of chemical adsorption is mainly caused by functional groups such as hydroxyl groups.
[0063] Under high temperature and high humidity conditions, the amount of gaseous iodine captured by porous carbon only decreased by 17.49%. The iodine loaded on porous carbon had a 7-day retention rate of 85.41% at room temperature and ambient pressure. After 5 cycles of use, the amount of iodine captured was still able to maintain 91.87% of the initial capacity. Its excellent resistance to high temperature and humidity, retention rate and reusability show broad application prospects.
[0064] Using agricultural waste walnut shell as biomass precursor, a biochar with high iodine capture performance was prepared by urea-assisted potassium hydroxide. The biochar could capture 3162 mg / g of gaseous iodine within 6 hours, while the sample without urea was only 2027 mg / g. The use of urea increased iodine capture by 55%. This method was applied to other biomass such as apricot shell, durian shell, sunflower flower disk, corn stalk and corn cob. The biochar obtained captured 5368 mg / g, 6177 mg / g, 5505 mg / g, 5518 mg / g and 6212 mg / g of gaseous iodine, respectively, proving the effectiveness of urea in promoting iodine capture performance. When the biochar after iodine capture was left to stand under air conditions, the iodine desorption rate was only 2.91% in 24 hours, and the cumulative desorption rate was 8.72% in 7 days, showing a good anti-desorption effect. The biochar was placed in aqueous solution and cyclohexane solvent for iodine capture, and its performance in 20 mg / L and 100 mg / L iodine solutions was better than that of nuclear-grade activated carbon.
[0065] The characterization and analysis results show that urea improves the pore structure of biochar and increases the specific surface area and pore volume of biochar. No increase in N content was detected in the biochar obtained by urea-assisted activation, and no obvious nitrogen-containing functional groups were observed, indicating that the original nitrogen components in the biomass and the added urea precursors at 800°C were converted into pore-forming effects rather than chemical affinity brought by heteroatom doping. The iodine capture and pore size analysis of biochar with different urea additions showed that hierarchical pores were the main reason for the high iodine capture performance of urea-assisted biochar. The iodine capture and DFT calculation results of carbon nanotubes with different pore sizes showed that the microporous structure in the hierarchical pores played a leading role in urea-assisted biochar iodine capture. This study provides a reference for the preparation of solid adsorption materials for high iodine capture, which can be used for the capture of iodine in radionuclides and the disposal of iodine waste from iodine-related factories.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0067] References: 1.XIE Ying, CHEN Hongyi, MEI Bingyu, et al. Construction of camphorleaves-derived biochar@bismuth for the capture of gaseous iodine[J]. ChemicalEngineering Science, 2023, 281: 119205. 2. LI Li, CHEN Run, LI Yarong, et al. Novel cotton fiber-covalentorganic framework hybrid monolith for reversible capture of iodine[J].Cellulose, 2020, 27(10): 5879-5892. 3. YANG Xiaoming, XIE Dong, WANG Weihao, et al. An activated carbonfrom walnut shell for dynamic capture of high concentration gaseous iodine[J]. Chemical Engineering Journal,2023,454(4): 140365. 4. SUN Hanxue, LA Peiqing, YANG Ruixia, et al. Innovative nanoporouscarbons with ultrahigh uptakes for capture and reversible storage of CO2andvolatile iodine[J]. Journal of Hazardous Materials, 2017, 321: 210-217. 5. LIU Sheng, ZENG Yiyang, ZHANG Ai, et al. Efficient capture ofradioactive iodine by ZIF-8 derived porous carbon[J]. Journal ofEnvironmental Radioactivity, 2022, 249: 106895-106895. 6. WANG Zhuang, HE Yi, ZHU Lin, et al. Natural porous wood decoratedwith ZIF-8 for high efficient iodine capture[J]. Materials Chemistry andPhysics, 2021, 258: 8. 7. YAN Zhuojun, YUAN Ye, TIAN Yuyang, et al. Addendum: HighlyEfficient Enrichment of Volatile Iodine by Charged Porous Aromatic Frameworkswith Three Sorption Sites. [J]. Angewandte Chemie (International ed. inEnglish), 2015, 54(48): 14215-14215. 8. MA Hui, CHEN Jinging, TAN Liangxiao, et al. Nitrogen-RichTriptycene-Based Porous Polymer for Gas Storage and Iodine Enrichment [J].ACS Macro Letters, 2016, 5(9): 1039-1043. 9. CHEN Dongyang, FU Yu, YU Wenguang, et al. Versatile Adamantane-based porous polymers with enhanced microporosity for efficient CO2captureand iodine removal[J]. Chemical Engineering Journal, 2018, 334: 900-906. 10. YAO Ruxin, CUI Xin, JIA Xiaoxia, et al. A Luminescent Zinc(II)Metal-Organic Framework (MOF) with Conjugated π-Electron Ligand for HighIodine Capture and Nitro-Explosive Detection[J]. Inorganic Chemistry, 2016,55(18): 9270-9275. 11. LIAO Yaozu, CHENG Zhonghua, ZUO Weiwei, et al. Nitrogen-RichConjugated Microporous Polymers: Facile Synthesis, Efficient Gas Storage, andHeterogeneous Catalysis[J]. Acs Applied Materials&Interfaces, 2017, 9(44):38390-38400. 12. ZHU Yunlong, JI Yajian, WANG Degao, et al. BODIPY-basedconjugated porous polymers for highly efficient volatile iodine capture[J].Journal of Materials Chemistry A, 2017, 5(14): 6622-6629. 13. LI Hui, DING Xuesong, HAN Baohang. Porous Azo-Bridged Porphyrin-Phthalocyanine Network with High Iodine Capture Capability[J]. Chemistry-aEuropean Journal, 2016, 22(33): 11863-11868。
Claims
1. A method for modifying the pore structure of agricultural waste biochar materials, characterized in that: Agricultural waste is crushed and sieved, and the obtained biomass is mixed with potassium hydroxide and a modified precursor aqueous solution, dried, and reacted at high temperature in an airtight condition, and the obtained product is washed with 0.1 mol / L hydrochloric acid and ultrapure water respectively and then dried; wherein: the modified precursor aqueous solution is a urea aqueous solution; the mass ratio of biomass to potassium hydroxide is 1:0.5-1:3, and the mass volume ratio of biomass to the modified precursor aqueous solution is 1:0.5-1:4; the temperature of the high temperature reaction is 300-900°C; and the heating rate of the high temperature reaction is 5°C / min.
2. The method according to claim 1, characterized in that: The agricultural waste is any one of walnut shells, apricot shells, durian shells, sunflower discs, corn cobs or corn stalks; the agricultural waste is crushed to 0.01-6 mm.
3. The method according to claim 2, characterized in that: The agricultural waste is walnut shells, which are crushed to 3-6 mm.
4. The method according to claim 1, characterized in that: The mass ratio of the biomass to potassium hydroxide is 1:1; the mass volume ratio of the biomass to the modified precursor aqueous solution is 1:3; and the temperature of the high temperature reaction is 800°C.
5. A modified porous biochar adsorbent obtained by the modification method according to any one of claims 1 to 4.
6. Use of the porous biochar adsorbent according to claim 5 in the capture and removal of radioactive iodine.
7. The use according to claim 6, characterized in that: The radioactive iodine is gaseous iodine, elemental iodine in aqueous solution or elemental iodine in cyclohexane.
8. The use according to claim 7, characterized in that: The radioactive iodine is gaseous iodine. The specific method is as follows: excess iodine and 0.02g of porous biochar adsorbent are placed in two small bottles respectively; then the two small bottles are placed in a large bottle; the large bottle is placed in a constant temperature box at 78°C to simulate the actual situation of nuclear fuel processing; the capture amount is determined by weight method, and the sample is weighed at regular intervals; By comparing the weight before and after capture, the capture amount of porous carbon is calculated; the calculation formula is: ; Where: q t is the adsorption capacity, mg / g; m t As porous biochar adsorbent t The mass of iodine adsorbed at each moment, g; m 0 is the initial mass of the porous biochar adsorbent, g.
9. The use according to claim 7, characterized in that: The radioactive iodine is elemental iodine in aqueous solution. The specific method is as follows: 0.1 g / L porous biochar adsorbent is added to 100 mL of elemental iodine aqueous solution with a pH of 5, the reaction solution is sealed and oscillated at a speed of 160 rpm at 25° C., after a certain time interval, the supernatant is taken out and filtered through a 0.22 μm membrane to remove the porous biochar adsorbent, and the iodine element concentration in the filtrate is measured at 460 nm using a UV-visible spectrophotometer.
10. The use according to claim 7, characterized in that: The radioactive iodine is elemental iodine in cyclohexane. The specific method is as follows: 0.4 g / L porous biochar adsorbent is added to 100 mL of cyclohexane solution of 100 mg / L elemental iodine, the reaction solution is sealed and oscillated at 160 rpm at 25°C, after a certain time interval, the supernatant is taken out and filtered through a 0.22 μm membrane to remove the biochar, and the iodine concentration in the filtrate is measured at 523 nm using a UV-visible spectrophotometer.
Citation Information
Patent Citations
Preparation method and application of modified biochar for adsorbing fluoride and cadmium ions in wastewater
CN112275253A
Biological carbon material for capturing iodine and treating organic wastewater as well as preparation method and application of biological carbon material
CN118527109A
A process for the preparation of tofu cookie and tofu cookie produced therefrom
KR1020250011299A
Cited By
Wastewater COD (Chemical Oxygen Demand) degradation method for enhancing Fenton reaction through biological activated carbon
CN120774545A